Connexin gene mutations among ugandan patients with nonsyndromic sensorineural hearing loss. (2nd May 2014) - Javidnia, Hedyeh; Carson, Nancy; Awubwa, Michael; Byaruhanga, Richard; Mack, David; Vaccani, Jean‐Philippe
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Congenital deafness occurs in approximately 1 in 1, 000 live births, and 50% of these cases are hereditary. Connexin mutations have been identified as the most common cause of hereditary hearing loss in many populations. The prevalence of this mutation in African patients has not been adequately studied. The objective of this study was to determine the prevalence of connexin 26 and 30 mutations in a population of hearing‐impaired patients from Uganda. Study Design This is an observational study. Methods Coding regions of both GJB2 and GJB6, noncoding exon 1 of GJB2, and 30 nucleotides of intronic sequence bordering the exons were analyzed in 126 subjects from Uganda with confirmed bilateral, severe‐to‐profound sensorineural hearing loss. All variants were analyzed for possible clinical significance using a combination of database searches and in silico tools. Results Complete sequence data were obtained on 115/126 individuals; 11 had only partial or no results. Only one reported pathogenic variant was found in GJB2 (c.208C>G; p.Pro70Ala) and none in GJB6. Three reported variants and two novel variants within intron 1 of GJB2 and two variants within exon 3 of GJB6 were also found. Conclusions None of the most common types of deletions in the GJB2 gene (c.35delG, c.167delT or c.235delC) were found in this large cohort of deaf children from Uganda. This prompts a search for genetic causes of deafness among this and other previously studied African populations. Level of Evidence NA Laryngoscope, 124:E373–E376, 2014